Rancang Bangun Aplikasi Pemesanan Tiket Tempat Wisata Berbasis Android Menggunakan Metode Extreme Programming - Muhammad Ramadhan; Muhamad Azrino Gustalika (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research aims to design and develop a tourist ticket booking application with Android base using Extreme Programming method, which was conducted in Bukit Barisan Selatan National Park, Lampung. The process of developing this application through several stages, namely planning, design, coding, testing, and distribution. Testing the application using the Black Box Testing method concluded that all features and functions of the application run well as expected without any errors. In the Blackox testing calculation above, a total percentage of 100% was obtained. Therefore it can be concluded that the Bukit Barisan Selatan National Park tour ticket booking application is indicated to be very feasible and can be used properly. This application is designed to make it easier for tourists to order tickets online and help the manager of Bukit Barisan Selatan National Park in managing tickets and visitors more effectively and efficiently. This application is also expected to improve visitor experience and comfort by providing complete tourist information and better accessibility. Suggestions for further development include the addition of more diverse payment methods, integration of automatic ticket output features in the form of barcodes and scans, and regular application maintenance to reduce potential errors. Thus, this application is expected to be an effective and efficient solution in ticket management and increase the number of tourist visits to Bukit Barisan Selatan National Park